Inorganic nanocarriers based on calcium carbonate and silica oxide for passive breast cancer targeting - Alisa S. Postovalova; Yulia A. Tishchenko; Vladislava A. Rusakova; Timofey E. Karpov; Nina V. Gavrilova; Anna S. Rogova; Irina A. Gorbunova; Alexander S. Timin (Chimica Techno Acta)
Nanoparticles (NPs) are widely used platforms for delivery of various biologically active compounds. Unfortunately, there is a lack of comprehensive investigations that would include a few types of NPs with different physicochemical parameters and their potential use as delivery systems in one tumor model. Therefore, to achieve therapeutic effect via nanocarrier with therapeutic agent, the properties of the developed NPs must be clearly defined. Herein, we report the development and modification of 99mTc and Cy5-labeled NPs based on calcium carbonate (CaCO3) and silica oxide (SiO2) to investigate in vitro and in vivo distribution on an example of a breast cancer model. We describe the synthesis and characterization of these NPs, including their morphology, size distribution, stability in biological media and cytotoxicity. Transmission electron microscopy (TEM), confocal laser scanning microscopy (CLSM), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FTIR), direct radiometry analysis, and histology were used to collect all data. The cellular uptake of NPs on 4T1 cell linewas shown in vitro and in vivo. As a result, we demonstrated that these NPs are non-toxic, biocompatible, and stable system to use for delivery of bioactive compounds into breast cancer.